CHALLENGES AND OPPORTUNITIES OF AUTHENTIC ASSESSMENT FOR READING COMPETENCE (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Reading competence is a foundational skill in education, crucial for students' academic success and lifelong learning. Traditional assessment methods, such as multiple-choice tests and standardized exams, often fail to capture the depth of students' reading comprehension and critical thinking skills.